Regulation of Heme Oxygenase and Its Cross-Talks with Apoptosis and Autophagy under Different Conditions in Drosophila - Terence Al L. Abaquita; Milena Damulewicz; Debarati Bhattacharya; Elżbieta Pyza (MDPI AG, 2021)
Heme oxygenase (HO) is one of the cytoprotective enzymes that can mitigate the effects of oxidative stress. Here, we found that the ho mRNA level oscillates in the brain of Drosophila melanogaster with two minima at the beginning of the day and night. This rhythm was partly masked by light as its pattern changed in constant darkness (DD). It followed a similar trend in the clock mutant per01 under light/dark regime (LD12:12); however, differences between time points were not statistically significant. In older flies (20 days old), the rhythm was vanished; however, 15 days of curcumin feeding restored this rhythm with an elevated ho mRNA level at all time points studied. In addition, flies exposed to paraquat had higher ho expression in the brain, but only at a specific time of the day which can be a protective response of the brain against stress. These findings suggest that the expression of ho in the fly's brain is regulated by the circadian clock, light, age, exposure to stress, and the presence of exogenous antioxidants. We also found that HO cross-talks with apoptosis and autophagy under different conditions. Induction of neuronal ho was accompanied by increased transcription of apoptosis and autophagy-related genes. However, this trend changed after exposure to curcumin and paraquat. Our results suggest that HO is involved in the control of apoptotic and autophagic key processes protecting the brain against oxidative damage.